Analysis of The Cash Waqf Linked Sukuk (CWLS) Model As An Instrument of Post Covid-19 National Economic Recovery - Tanya Arisa Setyomurni; Muh. Nashirudin (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
The purpose of this research was conducted in order to find out whether the National Economic Recovery Program (PEN) carried out by the Government during the Covid-19 pandemic could be supported by one of the sharia financial social innovations, namely Cash Waqf Linked Sukuk. This study uses a descriptive qualitative approach with the literature review method to review and analyze facts in the field, expert opinions, theories and previous research related to CWLS and its development potential. From the research results it is known that the role of Cash Waqf Linked Sukuk is in revitalizing the country's economy, where income from the sale of Cash Waqf Linked Sukuk can be used as a new source of financing for the country's development. Cash Waqf Linked Sukuk is expected to be able to reach the poor who are especially dealing with the Covid-19 pandemic by providing working capital funds from waqf funds, so that waqf funds can be utilized to be more productive